Pengembangan E-Modul berbasis Discovery Learning pada Materi Larutan Elektrolit dan Non Elektrolit Kelas X SMA atau MA - Visca Alisia Arianti; Rahadian Zainul (Edukimia, 2020)
This research aims to develop teaching materials in the form of e-modules that are valid and practical. The type of research used is research and development (R and D). The development model used is the 4-D model which includes 4 stages, namely the define, design, develop and disseminate. Research carried out until the development stage, namely the validity and practicality test. The instruments used were validity and practicality sheets. The e-module was validated by 6 validators, while the practicality test was conducted by 3 chemistry teachers and 30 students XI MIA 6 of SMAN 5 Padang. The results of the validity and practicality analysis showed a validity value of 0.840 with a very high category. The practicality value by students is 0.920 and the teacher is 0.841 with a very high category. Thus, e-module based on discovery learning on electrolyte and non-electrolyte solution materials in class X SMA or MA is valid and practical.